O Google Earth como procedimento metodológico na prática pedagógica da Geografia no Ensino Fundamental II - Vale, Thiago Souza (2014)
This thesis discusses the use of Google Earth as methodological procedure in the teaching and learning of geographical education to the students of Escola Estadual Caetano de Campo, held in the 1st half of 2013. The popularization and dissemination of geographical information targeted to the geographical information are increasingly present in brazilian public schools, and demand more skills of both teachers and students consequently. Therefore, the objectives of this research are articulated to the computer role, through the mosaic of satellite images of different landscapes at various scales and temporalities presented in the Google Earth software, as a teaching media resource in the learning of geography. This research shows the experimental-inductive methodological procedure being evaluated quantitatively and qualitatively. The content used for this experimental were: Cartography, Europe and Globalization according to the curriculum proposal of the São Paulo State. The results presented that the students challenged themselves to study new technologies, improving performance in activities and events, however they had difficulties in procedural actions inherent geographical reasoning, such as orientation and localization of the geographical phenomenas. These difficulties are the fact of students do not initially dominate the software language and academic needs undelveloped throughtout their basic training. Then, we consider that the use of Google Earth, as a didacting resource, in fact enhances the teaching and learning, and further reaserches should be required to investigate and propose adaptations of the software to be used as a teaching resource applied to geography education